Dostoevsky after Bucha - Podoksik, Efraim (Studia Rossica Posnaniensia, 2025)
This article challenges the widespread intuition that Dostoevsky would have become a leading apologist for the current Russia-Ukraine war, and for contemporary Russian imperialism in general. Without downplaying Dostoevsky’s imperialistic and chauvinistic statements as found both in his literary and journalistic works, this article argues that they should be read in light of the more fundamental ethical idea-feelings from which they were derived. The physiognomy of today’s Russian imperialism and the circumstances of the current war make it highly improbable that Dostoevsky would have arrived at similar imperialistic political conclusions. It is more likely that his idea-feelings would have caused him to adopt a radical anti-war stance.